Does Onsite Cytotechnology Evaluation Improve the Accuracy of Endoscopic Ultrasound-Guided Fine-Needle Aspiration Biopsy? - Fahad Alsohaibani; Safwat Girgis; Gurpal Singh Sandha (Canadian Journal of Gastroenterology)
BACKGROUND: Endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) is the preferred modality for the cytological diagnosis of various cancers. Onsite cytopathology interpretation is not available in most centres.